Keputusan Mahasiswa Pengunjung Perpustakaan MenjadiAnggota Upu Perpustakaan Universitas Gadjah Mada(Decision of Students Visiting Gadjah Mada University Libraryto be Library Members) - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak.Ilmu Sosial dan Ilmu Politik UGM, 2006)
ABSTRACT The student's decision to be the member of a library is an expression of their need od information. This decision is influenced by intern al and external factors, such as social, milieu and motivation. There are so many kinds of library in UGM: faculty, research center